2015
DOI: 10.4081/monaldi.2011.248
|View full text |Cite
|
Sign up to set email alerts
|

Management of Post-intubation and/or Tracheotomy Tracheal Stenoses

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This study showed that stent placement, with removal 1 year later, had a better effect on long-term stabilisation of tracheal patency in respect to balloon dilatation technique, also in patients with complex stenosis (19). The stent was a temporary item aimed at defending the airway calibre, till the fibrocicatricial process end, as reported by several authors (5)(6)(7)(8), and for this reason silicon stent was recommended because it could be easily removed, in respect to metallic or combined ones. Also in the study of D'Andrilli et al, restenosis after surgical intervention (8 cases) was treated with laser-assisted dilatation and silicon stent positioning (15).…”
Section: Comparison With Similar Researchessupporting
confidence: 52%
See 1 more Smart Citation
“…This study showed that stent placement, with removal 1 year later, had a better effect on long-term stabilisation of tracheal patency in respect to balloon dilatation technique, also in patients with complex stenosis (19). The stent was a temporary item aimed at defending the airway calibre, till the fibrocicatricial process end, as reported by several authors (5)(6)(7)(8), and for this reason silicon stent was recommended because it could be easily removed, in respect to metallic or combined ones. Also in the study of D'Andrilli et al, restenosis after surgical intervention (8 cases) was treated with laser-assisted dilatation and silicon stent positioning (15).…”
Section: Comparison With Similar Researchessupporting
confidence: 52%
“…Surgery is the first line of treatment for tracheal stenosis and leads to a high rate of success (2,3). In recent years, the interest for endoscopic treatment modalities has increased (4)(5)(6)(7)(8), with the aim to treat patients with benign subglottic stenosis not yet stabilized, avoiding the need of a tracheostomy, which would complicate surgical repair. Laser-assisted endoscopy, with or without stenting, has however rarely been used in subglottic stenosis for anatomical and technical reasons (9).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated procedures also are not recommended due to the risk of devascularization [ 6 ]. Some authors have reported a successful rate of 100% in cases of web-like stenosis and in few cases of complex stenosis, treated with endoscopic treatment as laser and stenting, and recommended these treatment in cases of high risk patients or excessive length stenosis not suitable for surgery [ 7 , 8 ]. Bourinet et al recently analyzed their experience with transcordal silicone stents in adult laryngotracheal stenosis reporting low morbidity and excellent clinical outcomes on long term follow up [ 9 ].…”
Section: Main Textmentioning
confidence: 99%
“…2%–3% of patients who undergo intubations and/or tracheostomy develop tracheal stenosis. [ 10 ] The tracheal stenosis is classified as simple, which is a soft, short segment web-like narrowing often limited to the mucosa only or complex stenosis, which is a hard, long-segment stricture with destruction of tracheal cartilages and fibrosis. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Multiple recent studies also stress on the use of endoscopic intervention in simple stenosis only. [ 10 15 ] It is important to highlight here that all our patients were having complex stenosis and 17 out of 18 patients had history of failed endoscopic interventions. Endotracheal prosthesis (stents) should not be used as a definitive treatment in benign tracheal stenosis.…”
Section: Discussionmentioning
confidence: 99%